Framework design for teaching and learning chemistry subject using visual concept maps / Izwan Wahhiddan - Wahhiddan, Izwan (2014)
This research proposes a multimedia teaching and learning prototype that applies Concept Maps for Chemistry subject. Multimedia offers an extraordinary focal point to improve learning environment and a decent information representation system which is Concept Maps is utilized to speak to Chemistry actualities in a visual and graphical structure. In learning Chemistry subject, understudies need to constrain themselves to envision and remember actualities, ideas, and process in wording to comprehend the subject. Hence, understudies see Chemistry as troublesome and extremely unexciting subject and hard to empower understudy's creative ability while they are attempting to develop their reason and judgment. The exploration's destinations are to outline a multimedia model application for showing and learning Chemistry subject, to apply Concept Maps as an apparatus in showing and learning module for multimedia model application and to assess the adequacy and the convenience of multimedia showing and learning Chemistry subject. The exploration approach utilized is ADDIE model which is the standard methodology in multimedia application advancement. A testing directed to assess the viability and the convenience of Multimedia Teaching and Learning Chemistry subject. The new option of showing and learning Chemistry subject is more powerful contrast with ordinary system since the respondents enhanced their execution. Understudies' recognition and conduct are additionally positive, thusly it is considered as a usable device to help understudies in showing and learning Chemistry subject.